«Los apóstoles de la patria» - Alejandro Quiroga Fernández de Soto (Mélanges de la Casa de Velázquez, 2004)
This article analyses how the official idea of Spain was communicated by the Army to the whole country during the dictatorship of Primo de Rivera. The Primo Rivera regime created a series of military institutions, the most prominent of which were the Delegados gubernativos and the Servicio Nacional de la Educación Física Ciudadana y Premilitar, with the aim of spreading its Spanish nationalist doctrine and of «educating» the masses in patriotic values. From studying how these institutions functioned, it can be inferred that the efforts of the Primo Rivera regime achieved the opposite of what they intended, producing a «negative nationalisation», in which growing popular opposition to the agents of the State who were spreading the official idea of the nation ran parallel to a rejection of the idea of Spain being defended by these agents.